Novel approaches to the synthesis of low-molecular derivatives of 1,2,4- triazole - M. V. Chudinov; A. V. Matveev; N. I. Zhurilo; V. V. Prostakova; V. I. Shvets (Тонкие химические технологии, 2011)
Routes of synthesizing 5-alkyl(aryl) derivatives of 1[H]-1,2,4-triazole-3-carboxylic acids were studied. A novel efficient method of preparing such compounds by cyclization of bis-acylated oxalamidrazones was suggested.